Thrombospondin-1 promotes cell migration, invasion and lung metastasis of osteosarcoma through FAK dependent pathway - Hu, Chuanzhen (Oncotarget, 2017)
Microenvironment at the metastatic locus usually differs greatly from that present in the site of primary tumor formation and it has a significant impact on the fate of the extravasated cancer cells. We compared gene expression signatures of primary tumors and lung metastatic tumors, and identified Thrombospondin-1 (TSP1) as highly up-regulated in the lung metastatic tumors. Immunohistochemical staining further indicated that TSP1 protein expression was higher in lung metastatic tumors compared to primary tumors in both osteosarcoma xenograft model and human clinical samples. TSP1 mRNA level is significantly associated with the Enneking stage of osteosarcoma and lung metastasis. TGF-β pathways could stimulate the TSP1 expression in osteosarcoma cells. Knockdown of TSP1 expression in osteosarcoma cells dramatically suppressed cell wound healing, migration and invasion. Treatment with recombinant TSP1 protein in osteosarcoma cells significantly promoted cell wound healing, migration and invasion. Meanwhile, suppression of TSP1 in osteosarcoma cells resulted in decreased pulmonary metastasis in vivo. Mechanistically, TSP1 increased expression of metastasis related genes, including MMP2, MMP9 and Fibronectin 1. TSP1 promoted osteosarcoma cell motility through the activation of FAK pathway. Taken together, our study provides evidence of the contributions of TSP1 to the lung metastasis of osteosarcoma and suggests that this protein may represent a potential therapeutic target for osteosarcoma lung metastasis.